2015
DOI: 10.1080/08927022.2015.1055741
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations for the prediction of the dielectric spectra of alcohols, glycols and monoethanolamine

Abstract: This version is available at https://strathprints.strath.ac.uk/54062/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 93 publications
3
33
1
Order By: Relevance
“…Another issue that warrants further exploration is the effect of scaling on the dynamic dielectric response of fluids 15,48 . Indeed, it has been recently shown that, at least for some fluids, classical non-polarizable models are able to describe the dynamic response over a wide range of frequencies, provided the simulation results are scaled to match the corresponding experimental static dielectric constant 48 . Application of our scaling approach to those systems would make for interesting future research.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue that warrants further exploration is the effect of scaling on the dynamic dielectric response of fluids 15,48 . Indeed, it has been recently shown that, at least for some fluids, classical non-polarizable models are able to describe the dynamic response over a wide range of frequencies, provided the simulation results are scaled to match the corresponding experimental static dielectric constant 48 . Application of our scaling approach to those systems would make for interesting future research.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the inability of most available empirical force fields to accurately predict the dielectric response of liquids, Cardona et al 2 suggested using the experimental values of static dielectric constants when computing the frequency-dependent dielectric spectra of these liquids using the Debye relaxation model 20 . Following this suggestion we used the experimental static dielectric constant of water to compute the dielectric spectra of water.…”
Section: Resultsmentioning
confidence: 99%
“…Our MD simulations of 50% mole‐fraction of MEG in water yielded a maximum H‐bond decay time of 60 ps (see τ R of Table ), which is in the same order as the reported dielectric relaxation time, but is not expected to be identical, since the relaxation time primarily is related to the dipole reorientation time. Using a different MD based method, the dielectric relaxation time for pure MEG at 298 K has been reported to be 87 ps when a Debye model was utilized and 71 ps when a Cole‐Davidson model was applied (where MEG was modeled using the OPLS force‐field) …”
Section: Resultsmentioning
confidence: 99%